(untitled) (Ameghiniana, 2013)
Bivalves and gastropods from Mid-Holocene Gable Island are studied by means of palaeocological, taphonomic and morphometric analysis. It is concluded that these species are representative of the marine mollusk paleocommunities of the Island. These species are the same that are living presently in the region. Although they could belong to a shallow and cold environment, morphometric shell differences were detected; they were probably produced in response to minor climatic fluctuations.